KOMITE MANAJEMEN RISIKO, EKSTERNAL TATA KELOLA DAN KINERJA PERUSAHAAN - Atikah, Siti; Muhsyaf, Saipul Arni; Ramadhani, Rahmi Sri; Uciawati, Uciawati (Jurnal Aplikasi Akuntansi, 2024)
Good corporate governance can increase the value of a company by implementing a commitment to achieve predetermined goals. One of these goals is meeting the expectations of investors, shareholders, and other stakeholders to achieve maximum profit. This study aims to provide empirical evidence regarding implementing the Risk Management Committee and its impact on company performance. Organizations, as systems, constantly interact with their environment, which is influenced by individual psychology. The study uses a sample of 100 companies listed on the Indonesia Stock Exchange out of 848 as of March 2023. The Risk Management Committee's characteristics are measured by the team leader's number of members and the leader's family affiliation with the company's management. The level of competitiveness is calculated using the Hirschman-Herfindahl index. Multiple regression tests were conducted to examine these variables. The results show that the number of risk management committees and family affiliations has a negative impact on firm value, while the level of competitiveness has a positive effect. However, only the family affiliation of the chairman of the risk management committee significantly affects firm value. The study's limitation lies in measuring the Risk Management Committee's characteristics, and further research is needed with different measurements. The results of this study can be helpful for investors when making investment decisions and for companies when presenting non-financial information.